CORRELATION OF SEVERITY OF VESICO-URETERAL REFLUX WITH RENAL SCARRING IN CHILDREN WITH RECURRENT URINARY TRACT INFECTIONS - Nawaz, Nadia; Hafeez, Farkhanda; Chaudhary, Adeela; Shehzadi, Uzma (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the correlation of severity of vesico-ureteral reflux with the frequency of finding renal scar in children with recurrent urinary tract infections.Study Design: Correlational study.Place and Duration of Study: Department of Paediatrics Nephrology, Children Hospital, Lahore, from Jan 2016 to Jun 2017.Methodology: Seventy children (140 kidney units) of 1 month to 10 years of age with ≥2 episodes of urinary tract infection within a period of 1 year and having vesico-ureteral reflux of Grade III, IV and V were included. Data of each kidney unit was taken regarding grades of vesico-ureteral reflux, number of urinary tract infection episodes, presence or absence of renal scar on dimercaptosuccinic acid scan. Data was analyzed using SPSS-22. Correlation between vesico-ureteral reflux severity and renal scarring was seen by Spearman rank correlation coefficient.Results: Out of total 70 patients, 37 (52.9%) were males and 33 (47.1%) were females. Out of 140 kidney units, 53 (37.8%), 48 (34.3%) and 39 (27.9%) had a vesico-ureteral reflux of grade-III, grade-IV and grade-V respectively. Renal scarring was present in 51 (36.4%) kidney units. Out of these, 11 (7.8%) were grade-III, 19 (13.6%) were grade-IV and 21 (15%) were grade-V vesico-ureteral reflux kidney units. With increasing severity of vesico-ureteral reflux, presence of renal scar increased (correlation coefficient = 0.279, p-value 0.001). Renal scarring was present in 25 (35.8%) of right sided and 26 (37.1%) of left sided kidneys. The positive correlation between vesico-ureteral reflux severity and renal scarring was significant in leftkidneys (p=0.002) but insignificant in right kidneys (p=0.11). Study also revealed significant positive correlation between vesico-ureteral reflux severity and number of urinary tract infection episodes (p